2001
DOI: 10.1590/s1415-47572001000100032
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of secondary metabolites in sugarcane

Abstract: A set of genes related to secondary metabolism was extracted from the sugarcane expressed sequence tag (SUCEST) database and was used to investigate both the gene expression pattern of key enzymes regulating the main biosynthetic secondary metabolism pathways and the major classes of metabolites involved in the response of sugarcane to environmental and developmental cues. The SUCEST database was constructed with tissues in different physiological conditions which had been collected under varied situation of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 27 publications
2
17
0
3
Order By: Relevance
“…2). An observed increase in anthocyanins is attributable to increased activity of two key enzymes, phenyl ammonia lyase (PAL) and chalcone synthease (CHS), leading to flavonoids and anthocyanin synthesis under high temperature (Oren-Shamir and Nissim-Levi 1999;França et al 2001;Sachray et al 2002). Although accumulation of anthocyanins was determined for the whole shoot, the most probable location of their synthesis is the epidermis, where they presumably shielded the underlying mesophyll tissues from heat-stress effects.…”
Section: Discussionmentioning
confidence: 99%
“…2). An observed increase in anthocyanins is attributable to increased activity of two key enzymes, phenyl ammonia lyase (PAL) and chalcone synthease (CHS), leading to flavonoids and anthocyanin synthesis under high temperature (Oren-Shamir and Nissim-Levi 1999;França et al 2001;Sachray et al 2002). Although accumulation of anthocyanins was determined for the whole shoot, the most probable location of their synthesis is the epidermis, where they presumably shielded the underlying mesophyll tissues from heat-stress effects.…”
Section: Discussionmentioning
confidence: 99%
“…Phenolic compounds were considered as by-products of metabolic alteration (Solecka 1997). The results investigations unequivocally suggest that phenols not only play a major role in defensive reactions of plants but also influence humans and animals that consume products enriched with phenolic compounds (Franca et al 2001;Amarowicz and Weidner 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Recent studies, have demonstrated that secondary metabolites, particularly phenolic compounds, perform important signaling and protective functions in plants. Environmental stresses often lead to intensive biosynthesis of phenolic compounds in plants and, as a consequence, they affect humans' and animals wellbeing [1][2][3]. It is noteworthy that the enhancement of plants' tolerance to adverse effects of environmental conditions would result in much higher yields obtained from the currently cultivated fields.…”
Section: Introductionmentioning
confidence: 99%